CARDIOPULMONARY RESISTANCE IN OBESE INDIVIDUALS DURING DIFFERENT AEROBIC EXERCISES - Xiao,Peng (2022)
ABSTRACT Introduction: Obesity is a major cause of chronic diseases such as cardiovascular and cerebrovascular diseases, cancer, and diabetes. Recent studies have reported that combined aerobic and anaerobic exercise effects are more effective for fat reduction. However, aerobic and anaerobic exercise have different fat reduction mechanisms. Comparing the intervention effects of different combinations of these exercises could provide an experimental basis for establishing an optimal protocol for weight loss. Objective: To study the effect of different aerobic exercise intensities on cardiorespiratory endurance in obese patients and its impact on fat loss. Methods: 18 obese female college students (BMI≥25) were randomly divided into two groups with different proportions of aerobic and anaerobic exercise. Bioimpedance data and BMI were collected for analysis. SPSS 25.0 software was used for statistics, with mean and standard deviation expressed for each index. Significance level at p<0.05 and highly significant set at P<0.01. Results: The weight, BMI, waist-to-hip ratio, and body fat content of the two exercise methods were positively changed before and after the experiment. This change had a very significant difference. Conclusion: There was no statistical difference in the interventions for the six weeks. Aerobic exercise can effectively improve cardiopulmonary function, and the benefits are directly proportional to the period practiced. Evidence Level II; Therapeutic Studies – Investigating the results.